THE INFLUENCE OF PRODUCT QUALITY AND CONSUMER PERCEPTION TO PURCHASE DECISION ON CANON DSLR CAMERA IN MANADO - Gunadi, Nikita Prisilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Marketing is very important to the success of the company, marketing is used by employers as a tool to influence consumers, especially in making a purchase of a product. Consumer purchasing decision is a very important activity for the company, as one goal obtaining profits to the company. This study aimed to determine the influence of product quality, and consumer perception to purchase decision on canon DSLR camera in Manado. Quality has a direct impact on the performance products and services and has a close relationship with the customer value and satisfaction. Consumers will reveal his behavior after the perception of what the decision will be taken in buying a product.Design research using survey, and research methods used multiple regression analysis method. It can be concluded Product Quality and Consumer Perception simultaneously influence the purchase decision Canon DSLR Camera in Manado. And in partial, Product Quality and Consumer Perception significantly influence the purchase decision Canon DSLR Camera in Manado. PT. Datascrib management need to improve product quality and perceptions of consumer, this can be done marketing activities to increase sales and market share. Keywords: product quality, consumer perception, and purchase decision